Research Note: Water applied direct-fed microbial reduced mortality in heat stressed broilers - van der Klein, S.A.S.; Bernardeau, M.; Gibbs, K.; Pál, L. (Poultry science, 2024)
Pressure to reduce the use of antibiotics in the poultry industry has intensified research on alternative solutions to support intestinal health, including but not limited to direct fed microbials (DFM). Heat stress is known to impact intestinal health and function. The aim of this study was to determine efficacy of a water applied DFM product on broiler performance during the summer period. One of two treatments were randomly allocated to 12 replicate floor pens each: a control treatment and a treatment provided daily with a dual strain DFM comprised of Lactobacillus acidophilus AG01 and Bifidobacterium animalis AG02 at 1 × 108 CFU/bird/d. Each pen contained 20 Ross 308 broilers. All birds were fed the same three-phased wheat- and soybean meal-based diets. Body weight, feed intake, feed conversion ratio, and mortality were measured at d 0, 10, 24, 35, and 42. Due to natural extreme external temperature conditions, all birds were subject to heat stress during the end of the grower phase up to and including the finisher phase. Temperature was on average 5°C higher compared to industry recommendation. No significant differences were found in growth performance between the control and DFM treatment, yet BW at d 42 in both treatments was reduced by 19% compared to the breed standard. The DFM treatment significantly reduced mortality among the birds. Overall mortality from d 1 to d 35 was reduced from 4.58% to 0.42% (P = 0.023) and overall mortality from d 1 to d 42 was reduced from 5.83 to 0.83% (P = 0.027). This was driven by the difference in heat-stress related mortality in the finisher phase from d 25 to d 42, where mortality reached only 0.44% in the DFM treatment versus 2.88% in the unsupplemented control treatment. Post-mortem analysis confirmed heat-stress related hypoxia. In conclusion, the dual strain DFM may have provided improved (intestinal) homeostasis and barrier function allowing increased resilience to heat stress in broilers.